Impact of a Nursing Skill‐Improvement Intervention on Newborn‐Specific Delivery Practices: An Experience from Bihar, India. Issue 4 (20th June 2016) - Das, Aritra; Nawal, Dipty; Singh, Manoj K.; Karthick, Morchan; Pahwa, Parika; Shah, Malay B.; Mahapatra, Tanmay; Chaudhuri, Indrajit
Abstract: Background: High neonatal mortality in India had previously been attributed to the low proportion of institutional deliveries. However, a significant rise in the proportion of facility‐based births over the last decade has not achieved the desired reduction in neonatal mortality possibly as a result of low‐skilled care at facilities. This study evaluated the effectiveness of "Mobile Nurse Training, " a knowledge‐based intervention for nurses to improve essential newborn‐specific delivery practices. Methods: Eighty health centers with obstetric care facilities were selected from eight districts of Bihar. The intervention teams were composed of two trained nurses who conducted a week‐long workshop per month at every health facility for 6 months. An independent evaluation team conducted baseline and postintervention assessments at every facility. The assessments included passive observation of newborn‐specific delivery practices and recording of results on a preformatted checklist‐based tool. Results: The intervention was associated with significant increases in the odds of four recommended practices: placing the newborn on mother's abdomen (adjusted odds ratio (AOR) 4.2 [95% CI 3.0–5.9]), wiping the eyes with sterile gauze (AOR 2.2 [95% CI 1.4–3.4]), skin‐to‐skin care (AOR 2.7 [95% CI 2.0–3.5]), and guidance for initiation of breastfeeding (AOR 1.6 [95% CI 1.2–2.1]). The intervention was also found to be positively associated with the summary score for improvements in all newborn‐specific delivery practices. One year after the intervention, the summary practice score remained higher than at baseline, but with some decline over time. Conclusions: The "Mobile Nurse Training" intervention provides a pathway for improving adherence to recommended newborn‐specific delivery practices among institutional birth attendants in rural Bihar.